The LEGO movie 2. the second part [videorecording (DVD)] - Rudolph, Maya; Ferrell, Will, 1967- (Warner Bros. Home Entertainment, 2019)
It's been five years since everything was awesome and the citizens are facing a huge new threat: Lego Duplo invaders from outer space, wrecking everything faster than they can rebuild.